Quantifying Exchange Rate Volatility and Financial Sensitivity in Indonesia’s Energy Transition Financing - Faqih Ahmad Muzakky (Penerbit Jurnal Indonesia, 2026)
Exchange rate risk remains a major financial barrier to long-term energy transition financing in emerging market economies. In Indonesia, renewable and clean energy projects are frequently exposed to currency mismatches, where revenues are predominantly denominated in Indonesian rupiah while capital expenditures and debt obligations are largely denominated in foreign currency, particularly the United States dollar. Previous studies emphasize that such mismatches significantly increase financial vulnerability in infrastructure projects (Siregar & Wihardja, 2023; OECD, 2024). This study quantitatively examines the magnitude of exchange rate risk and its implications for financial sustainability in Indonesia’s energy sector. Using historical USD/IDR data from 2014–2024, exchange rate volatility is estimated and integrated into a scenario-based sensitivity analysis applied to long-term financial projections. The results indicate that while Indonesia’s exchange rate volatility remains moderate relative to other emerging economies, its long-term financial implications are substantial when applied to large-scale, foreign-currency-funded energy investments. Sensitivity analysis further shows that exchange rate volatility, although less dominant than revenue growth, constitutes a critical risk factor for financial sustainability when combined with long-term funding exposure. These findings provide quantitative evidence supporting the need for structured currency risk management mechanisms in Indonesia’s energy transition financing.